Stormwater quality dynamics in a recovering forest of the upper Rasau catchment in Ayer Hitam Forest Reserve - S., Nurhidayu; N., Suhaidah (RSIS International, 2024)
Monitoring catchment water quality is crucial for maintaining safe water resources and supporting effective conservation and management strategies. This study evaluates stormwater quality in the Upper Rasau Catchment, located within the Ayer Hitam Forest Reserve (AHFR) in Klang Valley, Malaysia, under both baseflow and stormflow conditions. Key water quality parameters, including dissolved oxygen (DO), turbidity, total suspended solids (TSS), salinity, total dissolved solids (TDS), electrical conductivity (EC), pH, and temperature, were measured across 189 samples collected during 11 storm events between September 20, 2023, and February 24, 2024. The findings reveal that river responses were influenced by rainfall intensity, with most discharges occurring approximately 30 minutes after rainfall, highlighting the Ayer Hitam Forest Reserve’s ability to regulate water storage and flow. Descriptive analyses and classification based on the National Water Quality Standards (NWQS) indicated that Upper Rasau’s water quality typically falls under Class I, even during storm events, although pH levels dropped to Class III/IV during two storm events. Pearson’s correlation and simple linear regression analyses showed significant relationships between discharge and water quality parameters, and pollution load calculations estimated the total dissolved solids (TDS) and total suspended solids (TSS) produced during each storm event. Overall, the study suggests a significant improvement in the water quality of Upper Rasau, reflecting over 60 years of ecological recovery.